Línguas entrelaçadas : uma situação sui generis de línguas em contato - Braga, Alzerinda (2011)
ABSTRACT: In this study we highlight special characteristics of an unusual contact situation involving speakers of languages from different genetic origins, presently located in the Guaporé valley, Rondônia State – Wayurú, Makuráp, Tupari, Kampé (Tupari family, Tupian stock), Aruá (Mondé family, Tupian stock), Jeromitxí and Arikapú (Jabutí familly), Massaká (Aikaná), Kanoê and Kujubim (linguistic isolates). We discuss some of the social factors accounting for the contact among the speakers of these languages. We also comment on the network of relationships established between the speakers of these languages, which have contributed to the survival of the languages.